2020
DOI: 10.12775/jehs.2020.10.09.043
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the diet, microelements, macronutrients and vitamins on the schizophrenia – literature analysis

Abstract: Introduction: Schizophrenia is a disease that affects approximately 1% of the population. It begins in adult humans. It turns out that there are factors that predispose to schizophrenia, and by modifying your lifestyle, you can reduce the likelihood of its occurrence. One of such factors is the diet and microelements, macronutrients and vitamins that we consume every day. The aim of the study: The aim of this study was to find out the relationship between the diet, microelements, macronutrients, vitamins and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Dietary fiber, essential for digestion, may help prevent cardiovascular diseases [ 33 ] and improve mental health [ 34 ]. Fiber intake in both populations, with schizophrenic disorders and general populations, is lower than recommended [ 12 , 13 , 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary fiber, essential for digestion, may help prevent cardiovascular diseases [ 33 ] and improve mental health [ 34 ]. Fiber intake in both populations, with schizophrenic disorders and general populations, is lower than recommended [ 12 , 13 , 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies of various nutrients, most often vitamins, are linked to impaired cognition. B vitamins like cobalamin, thiamine, riboflavin, pyridoxine, folate, and niacin have been associated with a range of mental health conditions, from depression and poor memory to mania and psychosis [ 29 , 35 ]. The results of the present study showed that apart from folates, both beneficiaries’ and caregivers’ mean daily intake met the recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamins are often obtained through diet because many of them cannot be produced by the human body at sufficient levels. Many researchers have linked vitamin deficits to schizophrenia, either in the early stages of the condition or after diagnosis [60]. Vitamin B is necessary for cellular metabolism, which includes oxidation-reduction and trans-methylation [61].…”
Section: Importance Of Vitamins In Treatment Of Schizophreniamentioning
confidence: 99%